Something Got Your Tongue? A Unique Cause of Hypoglossal Nerve Palsy - Alan Tesson; Peter Kranz; Ali Zomorodi; Joel Morgenlander (Case Reports in Neurological Medicine)
Introduction. The authors report a rare cause of isolated hypoglossal nerve palsy caused by a high cervical osteophyte. This case increases clinical knowledge of an underreported condition and teaches the clinician radiologic pearls in making the diagnosis. To their knowledge, this is the first case report showing surgical remediation of this condition. Symptoms and Clinical Findings. A 73-year-old female presented with several months of occipital headache, progressive dysarthria, dysphagia, and tongue deviation to the right. Her neurologic exam was significant for atrophy of the right hemitongue with tongue fasciculations. On protrusion, her tongue deviated rightward. Diagnosis and Therapeutic Intervention. Careful review of her initial head computed tomography (CT) imaging revealed that a high cervical osteophyte caused unilateral, isolated hypoglossal nerve palsy. Neurosurgery performed a right, far lateral approach for decompression of this osteophyte and over the ensuing months her symptoms improved. Conclusion. High cervical osteophyte is an underrecognized cause of isolated hypoglossal nerve palsy. The imaging investigation should be systematic and focus on the skull base with magnetic resonance imaging (MRI) or CT. This is a rare occasion when high resolution CT of the skull base can actually be the more helpful imaging modality. As shown in this case, an osteoarthritic cause can be surgically ameliorated.